2007
DOI: 10.1016/j.jhsb.2006.08.019
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Sensory Recovery after Median Nerve Epair Using Cortical Audio–Tactile Interaction. A Randomised Multicentre Study

Abstract: __________________________________________________This is an author produced version of a paper published in Tidskriftstitel. This paper has been peer-reviewed but does not include the final publisher proof-corrections or journal pagination.Citation for the published paper: Rosén, B and Lundborg, G. "Enhanced sensory recovery after median nerve repair using cortical audio-tactile interaction. A randomised multicentre study. The "Sensor Glove System" offers an alternate afferent inflow from the hand early after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 45 publications
(58 reference statements)
0
22
0
1
Order By: Relevance
“…This concept is not new but there is very limited evidence to support this theory. [40][41][42][43][44] Based on neurobiological reasons we conclude and hypothesise that the pronounced difference between structural and functional capacities seen in the territory of the repaired nerve after a peripheral nerve injury cannot be avoided. However, it might be diminished with a revision of classical rehabilitation programs with use of guided cortical plasticity.…”
Section: Rosén Et Al 63mentioning
confidence: 85%
“…This concept is not new but there is very limited evidence to support this theory. [40][41][42][43][44] Based on neurobiological reasons we conclude and hypothesise that the pronounced difference between structural and functional capacities seen in the territory of the repaired nerve after a peripheral nerve injury cannot be avoided. However, it might be diminished with a revision of classical rehabilitation programs with use of guided cortical plasticity.…”
Section: Rosén Et Al 63mentioning
confidence: 85%
“…Several studies have already tested the use of other modalities to provide sensory feedback information. Visual feedback of hand force was shown to contribute to force control when stroke patients manipulate objects [19-23], and auditory feedback of finger tactile information was shown to contribute to the recovery of touch sensation after neural repair [56-58]. These results indicate that other feedback methods, such as mechanical, visual, and sound stimulation, may also help improve the manipulation capability of patients with severe sensory loss, and additional work is required to investigate which feedback method is more efficient.…”
Section: Discussionmentioning
confidence: 99%
“…In this context we emphasize the importance of the sensory glove, which in allowing alternative afferent impulses, that is, auditory impulses, to reach the cerebral cortex coming from the hand with altered sensitivity, enables greater preservation of the cortical map of the hand in an early post-injury phase and therefore better recovery of sensory function. 10 Some technical difficulties and limitations were encountered during the development of the equipment. The size of the container and of the materials, as well as the shielding of the circuit to enable studies involving magnetic resonance, were the main difficulties found.…”
Section: Discussionmentioning
confidence: 99%
“…The application and integration of different sensory stimuli soon after nerve repair have proven an effective method in the achievement of this goal. 2,3,9,10 The senses of hearing and touch are strongly related as they are based on the sensation of vibration, so that vibrational signals produced by touch, such as the sound of friction emitted by touching a certain texture, can be converted into vibroacoustic stimulation, causing the individual to "listen to what the hand feels", as described by Lundborg et al 1 The way in which the integration of sensory and hearing stimuli occurs in the sensory cortex, as well as the regions where it occurs, are not yet well known, 11,12 but it is known that this is present in many everyday situations. Accordingly, considering the diverse information about recovery of hand sensitivity and with a basis on the principle of the brain's capacity for integration of the tactile and auditory functions, 13 Lundborg et al 2 developed an artificial sensitivity system called the "sensory glove"; the model is not yet available on the market, hence the importance of making another model to enable the performance of more studies in the area.…”
Section: Introductionmentioning
confidence: 99%